Do Turkish Political Parties Pledge In Line With Their Party Family Ideologies? A Quantitative Analysis of Turkish Political Parties’ Manifesto Documents - İnan, Murat (Fırat University, 2023)
In the Western political science literature, modern political parties are grouped into party families, i.e., social democrat, socialist, communist, Christian democrat, liberal, radical, conservative, farmer-peasant, right-wing extremist, regional-ethnic parties and environmental movements. Categorizing a large number of political parties into a small number of party families is important not only for scientific reasons but also for practical ones. A correct categorization would help voters to better evaluate political parties and make more conscious voting decisions. Nevertheless, despite its central importance, the party family is one of the least empirically researched topics in the political science literature. More specifically, the literature on party family particularly lacks sufficient empirical investigations into the link between parties’ issue positions and their family locations. Moreover, to my knowledge, no previous study has investigated to what extent the Western party family phenomenon able to group political parties in a non-Western country. In order to fill this gap, this study aims to answer the following research question: Do Turkish political parties’ issue positions, as revealed in their manifesto documents, align with their expected party family locations? Answering this research question I hypothesize that Turkish political parties’ issue positions do not correspond to their expected party family locations. Results of the empirical analysis of the Manifesto Project data largely supported this hypothesis and one can now safely argue that Turkish political parties do not pledge in line with values suggested by the Western party family categorization.

In the Western political science literature, modern political parties are grouped into party families, i.e., social democrat, socialist, communist, Christian democrat, liberal, radical, conservative, farmer-peasant, right-wing extremist, regional-ethnic parties and environmental movements. Categorizing a large number of political parties into a small number of party families is important not only for scientific reasons but also for practical ones. A correct categorization would help voters to better evaluate political parties and make more conscious voting decisions. Nevertheless, despite its central importance, the party family is one of the least empirically researched topics in the political science literature. More specifically, the literature on party family particularly lacks sufficient empirical investigations into the link between parties’ issue positions and their family locations. Moreover, to my knowledge, no previous study has investigated to what extent the Western party family phenomenon able to group political parties in a non-Western country. In order to fill this gap, this study aims to answer the following research question: Do Turkish political parties’ issue positions, as revealed in their manifesto documents, align with their expected party family locations? Answering this research question I hypothesize that Turkish political parties’ issue positions do not correspond to their expected party family locations. Results of the empirical analysis of the Manifesto Project data largely supported this hypothesis and one can now safely argue that Turkish political parties do not pledge in line with values suggested by the Western party family categorization.
DO TURKISH POLITICAL PARTIES PLEDGE IN LINE WITH THEIR PARTY FAMILY IDEOLOGIES? A QUANTITATIVE ANALYSIS OF TURKISH POLITICAL PARTIES’ MANIFESTO DOCUMENTS
Keywords: Political Science Methodology; Siyaset Bilimi Metodolojisi